A chain mediation model on organizational support and turnover intention among healthcare workers in Guangdong province, China - Chen, Yuanyuan; Xia, Ping; Liu, Chaojie; Ye, Chumin; Zeng, Qi; Liang, Baofang (Frontiers in Public Health, 2024)
Introduction: The outbreak of the Corona Virus Disease 2019 pandemic has presented significant difficulties for healthcare workers worldwide, resulting in a higher tendency to quit their jobs. This study aims to investigate the correlation between organizational support, work-family-self balance, job satisfaction, and turnover intention of healthcare professionals in China's public hospitals. Methods: A cross-sectional survey was conducted on 5,434 health workers recruited from 15 public hospitals in Foshan municipality in China's Guangdong province. The survey was measured by organizational support, work-family-self balance, job satisfaction, and turnover intention using a five-point Likert scale. The association between organizational support, work-family-self balance, job satisfaction, and turnover intention was investigated using Pearson correlation analysis and mediation analysis through the PROCESS macro (Model 6). Results: Organizational support indirectly affected turnover intention through three pathways: the mediating role of work-family-self balance, job satisfaction, and the chain mediating role of both work-family-self balance and job satisfaction. Conclusion: Health administrators and relevant government sectors should provide sufficient organizational support, enhance work-family-self balance and job satisfaction among healthcare workers, and consequently reduce their turnover intentions.